The gastrointestinal bleeding in cirrhotic - Muñoz Monteavaro, Candido; Mescia, Carlos (Cirugía del Uruguay, 1974)
The author presents a series of 197 cirrhotic patients describing complications, urgency medica! treatment, urgency surgery and deferred medica! treatments, indicating figures and percentages. 147 presented digestive hemorrhages ( 76.5 % ) ; 2 had varices which had not bled for 8 years; 1 had 4 hemorrhages in 10 years; 34 bled from causes other than varices (23.2 % ) : 13 erosive gastroenteritis (necropsy), 3 gastric neoplasms, 3 due to corticoids, 4 due to ulcers. 56 of these patients died as a consequence of hemorrhages: 30 ( 53 6 % ) during the course of the first hemorrhage, 21 (37.7 % ) during the second and 5 ( 8.9 % ) during the third. 81 patients were examined for varices, by the following 3 techniques and with 79 % visualization: splenoportography 64.l % ) , esophagoscopy 61.7 % and esophagrogram 37 % . Bleeding was found in 10· out of a total of 25 cirrhotic patients with anachlorohydria ( 40 % ) and in 5 out of 6 with hyperchlorohydria ( 83.3 % ) . Urgency medica! treatment of acute hemorrhage consisted of Sengstaken-Blackemore's baloon ( effective in 68.57 % cases), octopressine in 57.14 % ) and in a combination of both procedures ,effective in 88.8 % of cases. Urgency surgery consisted of azygo-portal disconnection in 14 cases, successful in stopping hemorrhages in 43 % of cases; direct ligation of varices and limphovenous cervical anastomosis, ( effective in cases of accitis that do not respond to medica! therapy) which failed; urgency porto-cava anastomosis, an elective procedure in sorne cases. Deferred medica! treatment was applied in 103 cases. There were 62 venous shunts 18 splenorenal, 44 portocava; best results were those obtained with terminolateral porto-cava. 7 patients have survived for over 8 years, 80 % had no bleeding, 32 % developed postoperatory hepatic encephalopathies in various degrees, 1 developed bleeding duodenal ulcer 2 years after shunt was performed. The author favours prophylactic shunt.